2017
DOI: 10.1016/j.rbre.2016.07.009
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of the use of growth hormone in children and adolescents with juvenile idiopathic arthritis: a systematic review

Abstract: The majority of studies reported positive effects after the therapeutic use of GH, but some variability in response to treatment was observed. The combination of growth hormone with other drugs seems to be a good option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…A característica velocidade de crescimento abaixo do esperado esteve presente em 5,7% dos adolescentes. A velocidade de crescimento pode ser analisada em fases distintas, esse é o principal critério de normalidade, visto que esse é um processo dinâmico (21) . Destarte, essa é uma característica importante de ser avaliada pelos profissionais, visto que analisa uma série temporal e não uma medida isolada de tempo.…”
Section: Discussionunclassified
“…A característica velocidade de crescimento abaixo do esperado esteve presente em 5,7% dos adolescentes. A velocidade de crescimento pode ser analisada em fases distintas, esse é o principal critério de normalidade, visto que esse é um processo dinâmico (21) . Destarte, essa é uma característica importante de ser avaliada pelos profissionais, visto que analisa uma série temporal e não uma medida isolada de tempo.…”
Section: Discussionunclassified
“…Indeed, TNF-α and IL-6 inhibitors have been progressively more used in clinical practice, leading to a reduction of serious side effects, such as growth retardation and obesity, in children with JIA. However, contemporary literature on the biological era agrees that rhGH treatment provides good improvement in growth delay, with some variability ( 20 ).…”
Section: Delayed Puberty In Jia: Efficacy Of Rhgh Therapy On Pubertal...mentioning
confidence: 99%
“…However, there have been recent reports in the medical literature of cases in which treatment with biologics failed to restore normal growth velocity in patients with JIA, particularly in those with sJIA or those who required more than one biologic to control the disease (3,17). In contrast, several studies have reported improved height velocity and growth rates in JIA patients treated with recombinant human GH (rhGH) (12,(18)(19)(20). This study aimed to evaluate the impact of rhGH treatment on growth and pubertal development in patients with JIA through a narrative review of the literature over the last four decades.…”
Section: Introductionmentioning
confidence: 99%
“…The inadequate growth velocity and short stature frequently observed in children with JIA is routinely treated with recombinant human growth hormone (rhGH) [25,26]. Treatment with rhGH is associated with a plethora of side-effects, including JIA relapse [27], as the direct result of rhGH stimulation of the macrophage cytokines release which, in turn, is involved in the production of interferon-c (IFN-c) by the T lymphocytes [28].…”
Section: Recombinant Human Growth Hormone (Rhgh) Side-effectsmentioning
confidence: 99%